Stone Barrington: Hit List - Book 53 - Woods, Stuart (New York : G. P. Putnams Sons, 2020)
"Stone Barrington faces down a vengeful miscreant... When Stone Barrington finds his name on a hit list, he plans to lie low until the culprit is caught. But when this foe shows no signs of stopping until his deadly objective is realized in full, Stone is left with no choice but to face the problem head-on. Armed and alert, Stone joins forces with his most savvy connections to catch the perpetrator before the next strike. But it turns out this scum is an expert at evasion in more ways than one, and the international cat-and-mouse hunt that ensues has Stone questioning if he has become the predator or the prey..." --
Keywords: Barrington, Stone -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Fiction; Thrillers (Fiction); Thrillers (Fiction)